Factors causing delayed presentations of breast cancer among female patients in Sulaimani Governorate, Kurdistan region, Iraq - Alaa Abdulrazzaq Abdulkareem; Hawar Ali Ghalib; Mezjda Ismail Rashaan (BMC, 2023)
Abstract Background Since breast cancer (BC) has the best chance of being effectively treated when it is tiny and has not spread, encouraging early disease detection remains a fundamental goal in improving prognosis. Objective To quantify the magnitude of the delay in BC presentation as well as the contributing factors related to this delay. Patients and methods Data was collected at the Breast Diseases Treatment Clinic, Shar Teaching Hospital, Sulaimani, Iraq from January 2017 to December 2021 of 429 patients. A validated questionnaire was distributed to women about their demographics, health, and general awareness of the disease. The patient delay was calculated by collecting information on when they initially began experiencing symptoms and when they saw a doctor. We also gleaned information about the tumour's clinicopathological features from the patient's medical records. Results The participants' ages ranged from 24 to 85 years, with a mean of 49.6 ± 11. Most women were middle-aged (53.8%), from urban areas (80.2%), illiterate (41.7%), married (86.5%), housewives (79.0%), given birth to > 4 children (34%), practised breastfeeding (78.8%), and non-smokers (91.4%). Regarding patients' health behaviours, there were highly significant correlations between early and late presentation (p < 0.001). Concerning the patient's awareness of BC symptoms, there were highly significant correlations between early and late presentation (p < 0.001). In addition, the late presentation was strongly correlated with bilateral BC, lymph node involvement, inflammatory BC, grade III BC, and T4 status. Conclusions Our findings shed light on possible causes of late presentation and identified those at risk of delayed consultation. Our communities need to be educated about BC, and encouraging them for early detection decreases the incidence of advanced BC.